2019
DOI: 10.14202/vetworld.2019.1261-1265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a standardized 40% ellagic acid pomegranate (Punica granatum L.) extract on seminiferous tubule histopathology, diameter, and epithelium thickness in albino Wistar rats after heat exposure

Abstract: Background and Aim: It has long been known that the spermatogenic tissue is very sensitive to temperatures higher than its physiologic temperature and causing cessation of activity and resulting in sterility. This study investigated the effect of a standardized 40% ellagic acid extract of pomegranate on the histopathology, diameter, and epithelial thickness of seminiferous tubules in albino rats exposed to heat. Materials and Methods: Twenty-five male albino Wistar rats were randomized at 7-8 months of age to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
2
6
0
1
Order By: Relevance
“…Additionally, in the present study, treatment with ellagic acid significantly increased spermatogenic lineage which leads to a significant increase in the thickness of the seminiferous tubule epithelium and diameter. Utomo et al also reported that anthocyanin had a key role in ameliorating the oxidative stress that leads to maintaining the normal spermatogenesis and following preserve the spermatogenic cells [79]. Hence, enhanced epithelium thickness is related Rostami et al BMC Complementary Medicine and Therapies (2022) 22:170 to increased numbers of Sertoli and spermatogenic cells [79], which is similar to our results.…”
Section: Groupsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, in the present study, treatment with ellagic acid significantly increased spermatogenic lineage which leads to a significant increase in the thickness of the seminiferous tubule epithelium and diameter. Utomo et al also reported that anthocyanin had a key role in ameliorating the oxidative stress that leads to maintaining the normal spermatogenesis and following preserve the spermatogenic cells [79]. Hence, enhanced epithelium thickness is related Rostami et al BMC Complementary Medicine and Therapies (2022) 22:170 to increased numbers of Sertoli and spermatogenic cells [79], which is similar to our results.…”
Section: Groupsupporting
confidence: 90%
“…Utomo et al also reported that anthocyanin had a key role in ameliorating the oxidative stress that leads to maintaining the normal spermatogenesis and following preserve the spermatogenic cells [79]. Hence, enhanced epithelium thickness is related Rostami et al BMC Complementary Medicine and Therapies (2022) 22:170 to increased numbers of Sertoli and spermatogenic cells [79], which is similar to our results.…”
Section: Groupsupporting
confidence: 90%
“…This study showed that exposure to cigarette smoke two sticks per day could decrease the thickness of seminiferous tubules in the positive control group compared to the normal group, which is in accordance with a study by Putra (2014), in which the group exposed to cigarette smoke would have a decrease in the thickness of epithelial cells of seminiferous tubules due to dysfunction of the Sertoli and spermatogenic cells which inhibit spermatogenesis process. 18,19 Cigarette smoke contains various chemical substances which can induce the formation of free radicals (ROS) in the body. The testis is rich in polyunsaturated fatty acid (PUFA) and susceptible to free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate also improved the histological structure of testes with normal spermatogenesis, well preserved Sertoli cells and well delineated tubular basement membrane. The interstitium between tubules and Leydig cells was also intact (Utomo et al, 2019). The decline in the renal function is a well-known aspect of normal ageing (Kafetz, 1983), with decreased kidney function and glomerular filtration rate (GFR) (Denic et al, 2016).…”
Section: Discussionmentioning
confidence: 99%